The Role of Midwifery in Caring for Pregnant Women with Intrauterine Growth Retardation - Srisawad, Kanjana; Sangaroon, Pathanin (Journal of The Royal Thai Army Nurses, 2024)
Intrauterine growth retardation is defined as a newborn whose weight is less than the 10th percentile for that gestational age. It is a complication that can be found in pregnant women. Intrauterine growth retardation is classified into proportional and disproportionate growth retardation. There may be causes or risk factors from the pregnant woman, fetal and the placenta, which affect the pregnant woman and fetal, Therefore, midwifery an important role in caring for pregnant women with intrauterine growth retardation to caring pregnant women with intrauterine growth retardation. Preventing complications during pregnancy, labor and the postpartum period. Including, teaching or guiding clinical, consultation with health personnel, coordination, using empirical evidence and follow up and collect information about caring for pregnant women with preventing complications during pregnancy, labor and the postpartum period. Including applied to take care of pregnant women and their families for a quality pregnancy.